2021
DOI: 10.1177/0271678x21992625
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and transcriptional profiling reveals bioenergetic stress and activation of cell death and inflammatory pathways in vivo after neuronal deletion of NAMPT

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) is the rate-limiting enzyme in the NAD+ salvage pathway. Our previous study demonstrated that deletion of NAMPT gene in projection neurons using Thy1-NAMPT−/− conditional knockout (cKO) mice causes neuronal degeneration, muscle atrophy, neuromuscular junction abnormalities, paralysis and eventually death. Here we conducted a combined metabolomic and transcriptional profiling study in vivo in an attempt to further investigate the mechanism of neuronal degeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…The existence of the aforementioned metabolomics studies on tissues deficient in NAMPT, which catalyzes the NAD + synthesis step immediately prior to the NMNAT1-catalyzed step and exhibits dynamic subcellular localization (Svoboda et al, 2019), permits identification of potential NMNAT1-specific metabolic changes. Impaired glycolytic flux appears to be a more general feature of tissue NAD + depletion, as studies reporting NAMPT inhibition or deletion in projection neurons and skeletal muscle myotubes report accumulation of glycolytic metabolites upstream of GAPDH (Oakey et al, 2019;Lundt et al, 2021). Furthermore, utilizing stable isotope tracers, Lundt et al present evidence that glycolysis blockage reverses glycolytic flux in NAMPT-inhibited myotubes, an effect which we believe may explain decreased levels of G3P and DHAP in our model.…”
Section: Metabolic Defects In Nmnat1 Knockout Retinassupporting
confidence: 60%
See 1 more Smart Citation
“…The existence of the aforementioned metabolomics studies on tissues deficient in NAMPT, which catalyzes the NAD + synthesis step immediately prior to the NMNAT1-catalyzed step and exhibits dynamic subcellular localization (Svoboda et al, 2019), permits identification of potential NMNAT1-specific metabolic changes. Impaired glycolytic flux appears to be a more general feature of tissue NAD + depletion, as studies reporting NAMPT inhibition or deletion in projection neurons and skeletal muscle myotubes report accumulation of glycolytic metabolites upstream of GAPDH (Oakey et al, 2019;Lundt et al, 2021). Furthermore, utilizing stable isotope tracers, Lundt et al present evidence that glycolysis blockage reverses glycolytic flux in NAMPT-inhibited myotubes, an effect which we believe may explain decreased levels of G3P and DHAP in our model.…”
Section: Metabolic Defects In Nmnat1 Knockout Retinassupporting
confidence: 60%
“…Several recent studies examine levels of select metabolites in mature NMNAT1-deficient retinas (Sasaki et al, 2020a), or more broadly examine tissue metabolomes after perturbation of the NMN-synthesizing enzyme NAMPT (Lin et al, 2016; Oakey et al, 2019; Lundt et al, 2021). Our metabolomics results approximate that NMNAT1 synthesizes ∼40% of the total retinal NAD + pool, which is generally consistent with a previous model (Sasaki et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies examine levels of select metabolites in mature NMNAT1-deficient retinas ( Sasaki et al, 2020b ), or more broadly examine tissue metabolomes after perturbation of the NMN-synthesizing enzyme NAMPT ( Lin et al, 2016 ; Oakey et al, 2018 ; Lundt et al, 2021 ), but to date there have been no comprehensive metabolomic studies on NMNAT1-deficient tissues. Our metabolomics results approximate that NMNAT1 synthesizes ~40% of the total retinal NAD + pool, which is generally consistent with a previous model ( Sasaki et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies examine levels of select metabolites in mature NMNAT1-deficient retinas (Sasaki et al, 2020b), or more broadly examine tissue metabolomes after perturbation of the NMN-synthesizing enzyme NAMPT (Lin et al, 2016;Oakey et al, 2019;Lundt et al, 2021), but to date there have been no comprehensive metabolomic studies on NMNAT1-deficient tissues.…”
Section: Retinal Nmnat1 Loss Causes Diverse Metabolic Disruptionsmentioning
confidence: 99%
“…In line with these intracellular effects of NAMPT inhibition, neuron-specific deletion of intracellular NAMPT causes neuronal degeneration and led to muscle atrophy, paralysis, and eventually death in mice. Metabolomics of the cortical tissue of these mice revealed that NAMPT deletion activates apoptotic, inflammatory, and immune-responsive pathways and inhibits pathways involved in neuronal/synaptic function [ 156 ]. This supports the differential role of intracellular NAMPT as a key enzyme in cell metabolism and extracellular NAMPT as a signaling, cytokine-like molecule to activate inflammatory pathways.…”
Section: Adipokines As Therapeutic Target For Ms—evidence From Pre-clinical Studiesmentioning
confidence: 99%